Immune Cell-Derived Extracellular Vesicles – New Strategies in Cancer Immunotherapy - Yang, Pengxiang; Peng, Yong; Feng, Yuan; Xu, Zhuoying; Feng, Panfeng; Cao, Jie; Chen, Ying; Chen, Xiang; Cao, Xingjian; Yang, Yumin; Jie, Jing (Frontiers in Immunology, 2021)
Immune cell-derived extracellular vesicles (EVs) have increasingly become the focus of research due to their unique characteristics and bioinspired applications. They are lipid bilayer membrane nanosized vesicles harboring a range of immune cell-derived surface receptors and effector molecules from parental cells. Immune cell-derived EVs are important mediators of intercellular communication that regulate specific mechanisms of adaptive and innate immune responses. However, the mechanisms underlying the antitumor effects of EVs are still being explored. Importantly, immune cell-derived EVs have some unique features, including accessibility, storage, ability to pass through blood-brain and blood-tumor barriers, and loading of various effector molecules. Immune cell-derived EVs have been directly applied or engineered as potent antitumor vaccines or for the diagnosis of clinical diseases. More research applications involving genetic engineering, membrane engineering, and cargo delivery strategies have improved the treatment efficacy of EVs. Immune cell-derived EV-based therapies are expected to become a separate technique or to complement immunotherapy, radiotherapy, chemotherapy and other therapeutic modalities. This review aims to provide a comprehensive overview of the characteristics and functions of immune cell-derived EVs derived from adaptive (CD4+ T, CD8+ T and B cells) and innate immune cells (macrophages, NK cells, DCs, and neutrophils) and discuss emerging therapeutic opportunities and prospects in cancer treatment.